Analisis Kinerja Penjualan Risoles Melalui Program Kreativitas Mahasiswa Kewirausahaan (PKM-K) - Septy, Rosana Nabila; Hapsari, Dinda Tri; Mayrawanti, Nur Afifah Eka; Al Kautsarrani, Digma Lailil; Al’fiyah, Nur (Jurnal Ekonomi, Pendidikan dan Pengabdian Masyarakat, 2024)
This research is an in-depth analysis of the effectiveness of digital marketing strategies as a key instrument in increasing sales of risoles, particularly within the framework of the Student Creativity Program (PKM-K). The main focus of this research is to identify and evaluate the impact of the PKM-K program's contribution to increasing the visibility and consumer acceptance of risoles products. The research method applied involved careful analysis of sales data, including revenue results and total sales of risoles of each variant, with particular emphasis on exploring and implementing digital marketing strategies that support the promotion and distribution of Risol Hap risoles. The findings of this study reveal that the PKM-K program plays a significant role in opening up new opportunities for increased sales, and that digital marketing is an effective catalyst in reaching and building relationships with the target market. The word "PKM-K" is consistently at the core of this investigation, confirming that the sale of risoles is one of the initiatives of the program. This emphasis on the role of the PKM-K program provides an additional dimension to the study, by illustrating how students' creative achievements not only enrich academic aspects but also create a positive impact in the realm of marketing and selling culinary products such as risoles. By providing in-depth insights, this research makes a valuable contribution to the further development of the PKM-K program.